Growing experiments with a medicinal mushroom Agaricus blazei (MURRILL) - Geösel, A.; Győrfi, J. (International Journal of Horticultural Science, 2008)
The demand of natural and medicinal products has been increased for the past years. These products are often made from herbal and medicinal plants, and recently the mushroom products are much called. Nearby some well known species (like Lentinula edodes or Ganoderma lucidum) some not respected biomedicines are available in Hungary. Agaricus blazei (Murrill) is a Basidiomycota fungus, with almond-like taste and nice texture. This medicinal mushroom proved to be useful in cancer therapy and against some bacterial and viral diseases. In our experiment we tested 8 Agaricus blazei strains on fermented mushroom compost. The yields, average mushroom size, productivity and biological efficiency of the species were measured. Our data demonstrate that it is possible to get fruit bodies less than 2 months, and strain "837", "2603" and "MaHe" are suggested for further experiments. These strains gave the highest yield and efficiency in the cultivation.